Trimalchio’s Superstitions: Traditional Customs or Their Distortion? I - Keyer, Denis (Hyperboreus, 2024)
The author objects to H. Petersmann’s view that Trimalchio’s superstitious practice distorts common Roman customs and betrays his ignorance. The first half of the paper discusses two passages (Petr. 32. 3–4; 30. 5–6). (1) Petersmann erroneously states that Romans did not wear rings on their ring fingers and, relying on Plin. NH 28. 24, claims that Romans took off their rings during a meal. Yet, there is direct evidence for the opposite (Ov. Am. 1. 4. 26; Macr. Sat. 7. 13. 6), and for several reasons Pliny’s words nam si mensa adsit are likely to have been corrupt or misinterpreted. (2) Relying on Vitruv. 3. 4. 4 (on entering temples), Petersmann presumes that entering with the right foot forward was confined to sacred places, so that the prescript to enter Trimalchio’s  triclinium “dextro pede” renders divine honors to his house. Yet, passages like Ov. Ibis 101 with schol.; Apul. Met. 6. 26; Amm. Marc. 26. 6. 18 make it likely that not only temples, but also private houses were to be entered with the right foot forward.